Alzheimer’s Disease: What Can We Learn From the Peripheral Olfactory System? - Dibattista, Michele; Pifferi, Simone; Menini, Anna; Reisert, Johannes (Frontiers in Neuroscience, 2020)
The sense of smell has been shown to deteriorate in patients with some neurodegenerative disorders. In Parkinson’s disease (PD) and Alzheimer’s disease (AD), decreased ability to smell is associated with early disease stages. Thus, olfactory neurons in the nose and olfactory bulb (OB) may provide a window into brain physiology and pathophysiology to address the pathogenesis of neurodegenerative diseases. Because nasal olfactory receptor neurons regenerate throughout life, the olfactory system offers a broad variety of cellular mechanisms that could be altered in AD, including odorant receptor expression, neurogenesis and neurodegeneration in the olfactory epithelium, axonal targeting to the OB, and synaptogenesis and neurogenesis in the OB. This review focuses on pathophysiological changes in the periphery of the olfactory system during the progression of AD in mice, highlighting how the olfactory epithelium and the OB are particularly sensitive to changes in proteins and enzymes involved in AD pathogenesis. Evidence reviewed here in the context of the emergence of other typical pathological changes in AD suggests that olfactory impairments could be used to understand the molecular mechanisms involved in the early phases of the pathology.